Experimental comparisons of dynamic properties of floating wind turbine systems based on two different rotor concepts. (June 2016) - Duan, Fei; Hu, Zhiqiang; Liu, Geliang; Wang, Jin
Highlights: Gyroscopic effects of rotor rotation on yaw motions based on the TMBS and GMBS are investigated. An analysis of coupling effects between surge, pitch, and heave response behaviors is implemented based on an integrated wind-wave load case. Aerodynamic loading effects on motions in the TMBS and GMBS are studied. Dynamic characteristics of tower-top bending moments are investigated under both wind-only and combined wind-and-wave conditions. Axial rotor thrust and tower-top shear force response behaviors in the TMBS and GMBS are compared and analyzed. Mooring system response characteristics of the TMBS and GMBS are discussed based on wind-only and combined wind-and-wave load conditions. Abstract: This article presents research findings on the response characteristic differences between the thrust-matched blade system (TMBS) and the geometry-matched blade system (GMBS), which utilize redesigned thrust-matched and original geometry-matched blades, respectively, both based on the OC3 spar-type floating offshore wind turbine (FOWT). Particulars of this research are to examine the unique dynamic response characteristics of the TMBS, which includes a better performance-matched rotor relative to the GMBS. The response behaviors of the TMBS and GMBS are compared and studied based on a sequence of wind and irregular wave scenarios to reveal the unique roles that the thrust-matched rotor plays in the dynamic response behaviors of the floating wind turbine system. Gyroscopic effects of rotor rotation are found weakened in the TMBS, and yaw oscillation in the TMBS is not solely excited by rotor rotation, unlike in the GMBS. Coupling effects between surge and pitch are found in both the TMBS and GMBS under combined wind-and-wave condition. Furthermore, restraining effects of wind loads on motions in the GMBS and TMBS are both evident at natural frequencies while show distinct behaviors at the wave frequency. It is observed from the experimental measurements that the tower-top bending moment of the TMBS shows similar oscillation characteristics as that of the GMBS but with larger oscillation amplitudes. Furthermore, it is found that tower-top shear force and axial rotor thrust of the TMBS show distinct exciting motivators and much larger oscillation amplitudes relative to those of the GMBS. For both the TMBS and GMBS, the tensions measured in mooring lines are found to be coupled by yaw motion for wind-only cases while being clearly influenced by surge and heave couplings under integrated wind-and-wave load condition.